Pozytywna prognoza kryminologiczna jako materialna przesłanka warunkująca zastosowanie warunkowego zawieszenia wykonania kary. Uwagi na tle pojęcia „prognoza” oraz orzecznictwa sądów polskich - Witkowska-Rozpara, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The conditional suspension of the execution of the penalty is regulated in Chapter VIII of the Criminal Code of the Republic of Poland. One of the conditions of using this measure is positive criminological prognosis relating to the offender. This study presents the idea of criminological prognosis, the catalogue of factors examined by the court and the meaning of the term “criminological prognosis” in the courts’ opinion.
Keywords: zawieszenie wykonania kary; prognozy kryminologiczne